2011
DOI: 10.1118/1.3578608
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a novel algorithm for true 4D-VMAT planning with comparison to tracked, gated and static delivery

Abstract: Our investigation demonstrated that the 4D-VMAT system has the potential to improve radiation therapy of periodically moving tumors over 3D-VMAT, gating or tracking methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Our findings for the lung patient are consistent with their findings, which showed only slight reductions of dose to avoidance volumes for lung and liver patients using 4D-optimized photon beam tracking instead of photon beam gating. Similar to Chin and Otto (2011), we observed, in a phantom study, 4D optimization has a large ability to spare an avoidance volume near a moving target. In comparison with the approach of Graeff et al (in press), our method was similar in how we calculated the 4D dose contribution to each voxel from each ion pencil beam for each motion state and included these in 4D optimization.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings for the lung patient are consistent with their findings, which showed only slight reductions of dose to avoidance volumes for lung and liver patients using 4D-optimized photon beam tracking instead of photon beam gating. Similar to Chin and Otto (2011), we observed, in a phantom study, 4D optimization has a large ability to spare an avoidance volume near a moving target. In comparison with the approach of Graeff et al (in press), our method was similar in how we calculated the 4D dose contribution to each voxel from each ion pencil beam for each motion state and included these in 4D optimization.…”
Section: Discussionsupporting
confidence: 80%
“…Nohadani et al (2010) reported another 4D optimization approach for photon therapy that improved dose coverage compared to beam gating for lung cancer patients and reduced dose to healthy lung and was also more robust to irregular breathing than beam gating. Chin and Otto (2011) further demonstrated in phantom studies that 4D optimization can be applied to volumetric modulated arc therapy to spare avoidance volumes near a moving target. These studies suggest that the added degree of freedom, namely time, facilitates the optimization process and yields improved target dose coverage and to spare avoidance volumes near a moving target.…”
Section: Introductionmentioning
confidence: 96%
“…These effects additionally could be reduced by gating the treatment to a steady tumor position or tracking the moving tumor. Planning studies [14,15,8,16] and phantom studies [17,18] for comparisons between motion-management techniques have been performed previously. Planning studies are generally based on four-dimensional computed tomography data sets (4DCT), which provide patient-specific data for the dose calculation, but neglect actual capabilities of the delivery systems and are prone to motion artifacts [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such evidence tells us that if the relative distance of the PTV and OAR is considered when the apertures are morphed, OAR sparing may be improved. By using rigidly moving phantoms, Chin et al has studied and demonstrated the importance of considering the relative distance of PTV and OAR in 4D planning (Chin et al 2011). However, similar study has not been conducted for real patients with 4D CT, therefore, should be pending for the future.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of rigid motion simplified the registration matrix, and therefore the 4D-dose calculation. Another approach was proposed by Chin et al , which extended the Otto’s algorithm for 3D-IMAT to be used for 4D-IMAT planning (Otto 2008, Chin et al 2011). In their 4D algorithm, time-correlated beam samples were progressively added during optimization throughout the full range of a single arc.…”
Section: Introductionmentioning
confidence: 99%